ANALISIS KEUNTUNGAN USAHA PENGGILINGAN PADI â€œSEDERHANAâ€ DI DESA POOPO KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Jeri F. Momongan; Eyverson Ruauw; Noortje M. Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objective of this research is "Sederhana" rice milling businesses in one month. The data used is using profit analysis, namely by calculating the difference between revenue and costs used. The data collected will be presented in the form of variables and analyzed descriptively, then it will be measured by the Revenue Cost Analysis formula (R / C).Based on the results of the study, it is known that the net profit obtained by a simple rice mill when it is not harvest season is Rp. 16,058,083 and the net profit of a simple rice milling business during the harvest season is Rp. 72,584,583.This harvest season is valid for two productions in a year and profits in the harvest season for two months are 72,584,583 and for profits during the non-harvest season for 10 months 16,058,083 every year the average profit is Rp. 305,479,996 and for an average of Rp 25,479,166 per month.Keywords: Profit analysis- Rice milling